Analisis Alinyemen Horizontal dan Alinyemen Vertikal dengan Metode Bina Marga pada Ruas Jalan Tembesi - Aprijal, Aprijal; Yamali, Fakhrul Rozi; Setiawan, Ari (Jurnal Civronlit Unbari, 2025)
The development of information and communication technology (ICT) is driving the transformation of public services towards a more efficient, transparent, and accountable system. One example is the implementation of an application-based attendance information system, such as SiAbon, used by the Jambi Province Public Works and Public Housing Agency. This study aims to test the functionality of the SiAbon application using the Black Box Testing method to ensure that the available features meet user needs. The research method consisted of problem identification, data collection, analysis, design, and system testing. The test results focused on four main sections: the login page, the main page, the attendance page, and the current attendance page. Overall, the testing showed that the application's main functions ran according to specifications and were declared valid, although there were shortcomings in the support features that did not function optimally. The study concludes that the SiAbon application is suitable for use in supporting online employee attendance administration, but still requires regular improvements and maintenance to improve the system's quality and reliability in the future.